ANALISA PERBANDINGAN KONSUMSI LISTRIK PADA AC SPLIT1 PK MENGGUNAKAN FREON R32, R410A, DAN MC-22 - Din Aswan Ritonga; Muhammad Ilham; Ade Irwan (Jurnal Simetri Rekayasa, 2020)
One of the points stated in the Montreal and Kyoto protocol (1897 & 1997) is the elimination of the use of R-22 refrigerant (HCFC-22) and changing it with environmentally friendly refrigerants. The alternative is hydrocarbon refrigerants, which have been known since the early 1920s in refrigeration technology with other natural working fluids such as ammonia and carbon dioxide. One of the hydrocarbon refrigerants used in this study is Musicool (MC), which is produced by Pertamina's Processing Unit III Plaju. The purpose of this study was to determine the comparison of electrical energy consumption of AC Split 1 PK using 3 types of freon, namely R32, R410A, and MC22. The variables measured in this study were the working pressure of the refrigerant at the intake side of the compressor, voltage, electric current, and the testing time for 1 hour. Based on the analysis, it is obtained that the average split AC electricity consumption using freon R32 is 711.85 W, using R410A freon is 746.17 W, and using MC22 freon is 429.80 W. 301.85 kJ / kg, using R410A freon of 206.77 kJ / kg, using MC22 freon of 349.16 kJ / kg. The COP and EER AC Split values ​​are average using the R32 freon the COP value is 3.71 and the EER is 12.64, using the R410A freon the COP value is 3.55 and the EER is 12.09, and using the MC22 freon the COP value is 6.14 and EER of 20.94.